Study of EDTA intake of children for potential use of FeNaEDTA for breakfast cereal fortification - Galan, Maria Gimena (2012)
EDTA is used as disodium salt or disodiumcalcium in foods, to prevent lipid oxidation or as color and flavor stabilizer. In some countries, FeNaEDTA is also used as a source of iron for fortification. However, EDTA has an Acceptable Daily Intake (ADI) of 2.5 mg / kg/day. The aim of this study was to estimate the intake of EDTA in children of school age and the potential use of FeNaEDTA as iron source for breakfast cereal fortification. A qualitative-quantitative food frequency questionnaire was conducted on 225 schoolchildren of both sexes, aged between 4 and 13, from school canteens, public and private schools, from the city of Santa Fe (Argentina). Only those foods which EDTA addition is allowed in Argentina: packaged ice cream, soda, soft drinks and powdered soft drinks (upper limit of Na2EDTA o Na2CaEDTA: 35 mg/kg) and dressings and margarines (upper limit of Na2CaEDTA: 75 mg/kg) were considered. EDTA Average Daily Consumption (ADC) was 0.06 mg/kg/day with a median of 0.011 mg/kg/day, representing 2.4% of the ADI. In the hypothetical case that FeNaEDTA would be used as iron source for breakfast cereal fortification at level of 11 mg Fe%, the potential EDTA ADC would be 0.46 ± 0.32 mg/kg/day, representing 18.4% of the ADI (2.5 mg/kg/day). Results indicate that children from Santa Fe city have an EDTA ADC currently well below the maximum ADI of EDTA, which would remain low even if FeNaEDTA is used for breakfast cereal fortification.